Pengaruh disiplin kerja dan motivasi terhadap kinerja karyawan nimbuspost di Jakarta - Asmalah, Lia; Yudho, Pramono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of work discipline on employee performance, to determine the effect of motivation on employee performance, to determine the effect of work discipline and motivation on employee performance at NimbusPost. This type of research uses a quantitative associative approach by testing hypotheses, the population in this study is 182 employees from NimbusPost during 2021 and obtained a sample of 65 respondents with a sampling technique with a significance level of 10%. Data were obtained by distributing questionnaires of 30 statements. The results of the study, namely the Work Discipline Variable on the t test results obtained tcount 12.119 > ttable 1.669 and a significance value of 0.000 <0.1 then Ho was rejected and Ha was accepted. The variable of work motivation on the results of the t test obtained the results of the tcount value of 13.640 > ttable 1.669 and a significant value of 0.000 <0.1 then Ho was rejected and Ha was accepted. Work Discipline and Work Motivation Variables on the f test results obtained fcount 101.180 > ftable 4.00 and a significance result of 0.000 <0.1 then Ho is rejected and Ha. From the results of the analysis concluded that work discipline and motivation partially and simultaneously have a significant influence on employee performance at NimbusPost.